FACTORS OF DYNAMICS AND DEVELOPMENT TENDENCIES OF INTERNATIONAL TRADE - A. Rudneva (Вестник университета)
In the article the modern endogenous and exogenous factors of dynamics of international trade are analyzed at the present stage. The particular emphasis is placed on identification of trends of change of its commodity and geographical structure. Speeding up of positions of the certain countries, including the high-growth economies, their geoeconomic interests define the new horizons of the world economic interactions and also promote to arise the conditions for transformation of the existing world order in which formation Russia, among other players, will participate.